Correlates of laboratory-confirmed measles in Japan, 2011–2015. Issue 13 (22nd March 2019) - Watanabe, Aika; Shimada, Tomoe; Takahashi, Takuri; Arima, Yuzo; Kinoshita, Hitomi; Saitoh, Takehiko; Kanou, Kazuhiko; Matsui, Tamano; Sunagawa, Tomimasa; Tanaka-Taya, Keiko; Oishi, Kazunori
Highlights: A study was conducted to identify correlates of laboratory-confirmed measles. Epidemiological link had the highest association with laboratory-confirmed measles. International travel and lack of vaccination were also significantly associated. Our findings can help physicians improve their measles diagnosis. Abstract: Background: With the progressive decline in the incidence of measles in Japan, its diagnosis has become challenging, with fewer physicians having experience in examining measles patients. We aimed to determine the correlates of laboratory-confirmed measles to help physicians improve their measles diagnosis. Methods: This study was conducted using the National Epidemiological Surveillance of Infectious Disease (NESID) system data during 2011–2015. Among clinically suspected measles patients reported to NESID, measles virus (MV)-positive patients were compared with MV-negative patients. The odds ratios (OR) and associated 95% confidence intervals (CI) were determined using logistic regression. Results: A total of 4168 laboratory-tested patients were notified to NESID. We analysed 618 MV-positive patients (median age, 17 years; interquartile range [IQR], 4–30 years) and 600 MV-negative (median age, 10 years; IQR, 1–29 years) patients after excluding those that met the exclusion criteria or were reported during the rubella epidemic period (the 18th epidemiological week of 2012 to the 46th week of 2013). Having an epidemiological link with a measles patient within 14 days of onset (OR, 14.9; 95% CI, 10.0–23.3), a history of recent international travel (OR, 11.7; 95% CI, 6.9–19.9), and unvaccinated/unknown vaccination status for measles-containing vaccine (MCV; OR, 3.7; 95% CI, 2.3–5.7) were significantly associated with MV-positive status. International travel (adjusted OR, 10.2; 95% CI, 5.9–17.7) and unvaccinated/unknown MCV vaccination status (adjusted OR, 5.8; 95% CI, 3.5–9.8) remained significantly associated with MV-positive status after adjusting for age, sex, and each other. Conclusion: In low-incidence Japan, having an epidemiological link, international travel, and lack of MCV vaccination were correlates of laboratory-confirmed measles. The findings of this study could potentially improve the clinical diagnosis of measles, which can lead to more efficient testing and earlier laboratory confirmation.